Pembatalan Peminangan Akibat Adanya Adat Pulang Bainduok (Studi Kasus di Desa Sungai Liti Kecamatan Kampar Kiri Kabupaten Kampar) Persfektif Hukum Islam - Hayati, Yassir; Febiana, Fenni (Published by Institut Teknologi Pendidikan Indonesia, 2023)
Marriage is the longest scenario in life and marriage in Islam is more than just a civil contract. Compilations of Islamic law must emphasize that obeying Allah's instructions is a binding contract. This research uses ethnographic methods with a qualitative approach (field research) as well as normative theology and sociology, in the form of written data sources (library research) and documentation. The population in this writing is 8 people consisting of ninik mamak, traditional leaders and local ustad, and the sample consists of 4 couples or families. This writing shows that, firstly, there is a custom in Sungai Liti village, namely returning to the bainduok before the marriage proposal takes place, secondly there is a cancellation of the marriage proposal due to the custom of returning to the bainduok which costs a lot of money to get a new induok.